The association of body composition and fat distribution with hypertension in community-dwelling older adults: the Bushehr Elderly Health (BEH) program - Mohammad Mehdi Khaleghi; Ali Jamshidi; Sima Afrashteh; Hadi Emamat; Akram Farhadi; Iraj Nabipour; Zahrasadat Jalaliyan; Hasan Malekizadeh; Bagher Larijani (BMC, 2023)
Abstract Background A significant proportion of the global burden of disability and premature mortality has caused by hypertension. It seems that the relationship between obesity and hypertension is not only associated with excessive body fat mass (FM) but also with body adipose distribution patterns. The present study investigated the association between regional fat distribution using dual-energy X-ray absorptiometry and hypertension in older adults. Methods This cross-sectional study was performed using the data from Bushehr Elderly Health Program (BEH) on a total of 2419 participants aged 60 and over. Hypertension was defined as SBP of at least 140 mmHg and/or DBP of at least 90 mmHg. SBP between 120 and 139 mmHg and/or a DBP between 80 and 89 mmHg were considered prehypertension. Participants underwent body composition measurement by dual-energy x-ray absorptiometry to analyze FM, fat-free mass (FFM) in trunk and extremities composition. Results The results showed that 460 (19.02%) of participants had prehypertension, and 1,818 (75.15% ) had hypertension. The odds of having prehypertension (OR: 1.06, 95%CI: 1.01-1.12) and hypertension (OR: 1.08, 95%CI: 1.03-1.13) increased with a rise in total body FM percentage. Moreover, people with a higher FM to FFM ratio had increased odds of being prehypertensive (OR: 9.93, 95%CI: 1.28-76.99) and hypertensive (OR: 16.15, 95%CI: 2.47-105.52). Having a higher android to gynoid FM ratio was related to increased odds of being prehypertensive and hypertensive. Conclusions This study showed that a higher body FM, particularly in the android region, is associated with higher odds of having hypertension in older adults.